Isolation, characterization of specific bacteriophages and their effectiveness as biocontrols on raw seafoods contaminated with Vibrio parahaemolyticus - Tan, Chia Wanq (2021)
Vibrio parahaemolyticus is among the leading foodborne pathogens that can cause gastroenteritis, wound infections, and/or septicaemia in humans. Antimicrobial resistance also poses a significant global health issue. Research on alternative approaches such as the application of bacteriophage has become a potential solution to minimize the use of antibiotics. In this study, the prevalence and antibiotic-resistant patterns of V. parahaemolyticus were determined, and V. parahaemolyticus bacteriophages naturally present in seafood samples were isolated and characterized in detail. The genome of bacteriophages was later sequenced through whole-genome sequencing, followed by genome annotation. Finally, the characterized bacteriophages were used as a biocide to control the growth of V. parahaemolyticus in the food samples. According to the results, blood clams were detected at the highest prevalence rate (91.43%), followed by shrimp (88.57%), surf clams (82.86%), and squid (80.00%). Besides, 90.83% of the V. parahaemolyticus isolates were detected to be multidrug-resistant (MDR). Six V. parahaemolyticus species-specific bacteriophages were isolated from blood clam, shrimp, and surf clam samples. Morphological analysis revealed that bacteriophages ɸVp33, ɸVp22, ɸVp21 and ɸVp02 isolated from the shrimp samples belonged to the Podoviridae family. Bacteriophages ɸVp08 and ɸVp11 isolated from the blood clam and surf clam samples, respectively, were categorised into the Siphoviridae family. The optimal MOI for bacteriophage propagation was determined to be in the range of 0.001 to 1. The latent period of bacteriophages falls in the range of 10 to 20 min, and the burst size was approximately 17 to 51 PFU/cell. All bacteriophages were optimally stable over a wide range of temperature levels (20 to 50⁰C) and pH levels (5 to 11). After the whole-genome sequencing analysis, the genome of bacteriophages was detected to be between 42,896 and 76,128 bp, with a GC content of 48.93 to 49.33%, and 47 to 101 open reading frames (ORFs). The annotation of each predicted sequence revealed the presence of functional groups such as DNA regulation, structure, packaging, host lysis, hydrolysis, conjugation, and oxidation-reduction. In terms of the biological control application, bacteriophage suspensions achieved an average log reduction of V. parahaemolyticus in 2.85 ± 0.07 to 4.81 ± 0.14. Bacteriophage cocktails were observed to have an improved in vitro lytic activity compared to a single bacteriophage suspension. Oyster meat samples artificially contaminated with V. parahaemolyticus and treated with the bacteriophage cocktail also noticed a significant bacterial load reduction (P < 0.05) of 2.77 ± 0.53 to 3.07 ± 0.03 log CFU/g after 48 h of treatment. In conclusion, bacteriophages ɸVp33, ɸVp22, ɸVp21, ɸVp02, ɸVp08, and ɸVp11 isolated from the seafood samples demonstrated strong lytic activity against the growth of V. parahaemolyticus. Two bacteriophage cocktails (cocktail A and B) used in the inhibition of biofilm and biocontrol agents in food were found to have statistically significant effects in the reduction of biofilm formation and microbial loads of V. parahaemolyticus on the oyster meat samples. Bacteriophages in this study consequently proved to be practicable as biocontrol agents for the control of V. parahaemolyticus.